A changing market for PFI financing: Evidence from the financiers. Issue 3 (September 2015) - Demirag, Istemi; Khadaroo, Iqbal; Stapleton, Pamela
Abstract Responses to a questionnaire survey received from PFI financiers, and interviews with senior managers, show that as the credit crunch took hold banks became more risk averse. The prediction of Toms et al. that collusion between the state and the private sector might cease in the face of austerity does not appear to have occurred. Rather the state has intervened to benefit the private sector. We argue that two successive UK Governments intervened in the market to protect the role of private finance in PFIs but whether such interventions represent value for taxpayers' money is a question for future research.